1992
DOI: 10.1002/art.1790050208
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness levels in children with polyarticular juvenile rheumatoid arthritis

Abstract: Children with juvenile rheumatoid arthritis (IRA) often exhibit fatigue and prolonged exercise recovery. Improved fitness through physical conditioning has not been a goal of standard medical or physical treatment regimens for IRA, and fitness levels of children with IRA have rarely been studied. We compared physical fitness in 20 6 to 11-year-old patients with polyarticular JRA with sex-, age-, and size-matched controls, using the Health Related Physical Fitness Test (HRPFTJ, (I national, standardized, norm-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…As the child develops and grows, they may be excluded from learning new skills, such as hopping, running, jumping, climbing and skipping or joint movements may be adapted so that function and independence are impaired. [3][4][5]7 Children with JIA may be less fit [15][16][17] and active 18 than healthy children, and functional limitations and pain may affect their ability to perform some physical or social activities as more energy and effort are required. 19,20 Evidence to date Hydrotherapy and land-based physiotherapy treatments are designed to increase range of motion, muscle strength, physical fitness, quality of life (QoL) and function, in addition to reducing pain.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%
“…As the child develops and grows, they may be excluded from learning new skills, such as hopping, running, jumping, climbing and skipping or joint movements may be adapted so that function and independence are impaired. [3][4][5]7 Children with JIA may be less fit [15][16][17] and active 18 than healthy children, and functional limitations and pain may affect their ability to perform some physical or social activities as more energy and effort are required. 19,20 Evidence to date Hydrotherapy and land-based physiotherapy treatments are designed to increase range of motion, muscle strength, physical fitness, quality of life (QoL) and function, in addition to reducing pain.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%
“…As mentioned previously, attending physical education classes is a predictor of well-being for children with chronic arthritis (Sällfors et al, 2004), but physical fitness cannot be maintained at the same level as for non-disabled peers, if at all. Studies indicate that children with arthritis are less active physically, in general, than their peers (Klepper, Barbee, Effgren & Singsen, 1992;Hendersson, Lowell, Specker & Campaigne, 1995;Sällfors et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A later study by the same investigators reported decreased exercise time, lower peak heart rate, and higher metabolic cost for submaximal exercise in 30 children with JRA compared with healthy controls (10). Klepper et al (11), using the standardized Health Related Physical Fitness Test (HRPFT) (12), reported significantly lower scores on the 9-minute run-walk test of aerobic endurance in 20 children with polyarticular JRA, ages 6 -11 years, compared with healthy controls. No significant relationship was found between low fitness scores and measures of disease severity in any of these studies, suggesting deconditioning may be multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Moncur et al (16) reported increased maximal aerobic capacity and exercise time and decreased swollen joint count (JC) in 7 adolescents and young adults with JRA following 12 weeks of stationary cycling. Klepper and colleagues (17) found improved performance on the HRPFT 9-minute walk-run test in 5 children and adolescents after 6 weeks of low impact aerobic dance. Aside from these findings, little is known about the effects of specific modes of exercise on the joints of children with JRA.…”
Section: Introductionmentioning
confidence: 99%